High concentrations of atmospheric ammonia induce alterations of gene expression in the breast muscle of broilers (Gallus gallus) based on RNA-Seq. (December 2016) - Yi, Bao; Chen, Liang; Sa, Renna; Zhong, Ruqing; Xing, Huan; Zhang, Hongfu
Abstract Background High concentrations of atmospheric ammonia are one of the key environmental stressors affecting broiler production performance, which causes remarkable economic losses as well as potential welfare problems of the broiler industry. Previous reports demonstrated that high levels of ammonia altered body fat distribution and meat quality of broilers. However, the molecular mechanisms and metabolic pathways in breast muscle altered by high concentrations of ambient ammonia exposure on broilers are still unknown. Results This study utilized RNA-Seq to compare the transcriptomes of breast muscles to identify differentially enriched genes in broilers exposed to high and low concentrations of atmospheric ammonia. A total of 267 promising candidate genes were identified by differential expression analysis, among which 67 genes were up-regulated and 189 genes were down-regulated. Bioinformatics analysis suggested that the up and down-regulation of these genes were involved in the following two categories of cellular pathways and metabolisms: Steroid biosynthesis (gga00100) and peroxisome proliferator-activated receptor (PPAR) signaling pathway (gga03320), which both participated in the lipid metabolism processes. Conclusions This study suggests that longtime exposure to high concentrations of aerial ammonia can change fat content in breast muscle, meat quality and palatability via altering expression level of genes participating in important lipid metabolism pathways. These findings have provided novel insights into our understanding of molecular mechanisms of breast muscles exposed to ammonia in broilers. This study provides new information that could be used for genetic breeding and nutritional intervention in production practice of broilers industry in the future.